Gambaran Faktor Risiko Terhadap Keluhan Gangguan Otot Rangka Akibat Kerja (GOTRAK) pada Pekerja Pengangkut Gula di PT. X - Nurani, Ilmi Tri; Sunaryo, Merry; Ratriwardhani, Ratna Ayu; Ayu, Friska (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
In sugar porters at PT. X, manual handling is still performed using the shoulder and upper back. This study aims to describe the risk factors for musculoskeletal disorders (MSDs) among sugar porters at PT. X. This study uses a cross-sectional design with 41 respondents. Data were collected through observation, interviews, and filling out questionnaires related to work fatigue and MSD complaints based on the Indonesian National Standard (SNI) 9011:2021. The results showed that the majority of workers were aged 19-44 years (57%) and had worked for more than 5 years (73%). Most workers are in the very dangerous category for the musculoskeletal system (57%). MSD complaints with a high risk were found in the shoulders, upper back, and legs. The most frequently reported MSD complaints were in the shoulders, upper back, and legs. Factors such as age, work posture, length of service, and work fatigue were found to be associated with MSD complaints. This study emphasizes the importance of implementing proper ergonomics in the workplace to reduce the risk of MSD complaints. It is recommended to provide training on correct work postures, the use of lifting aids, and increase social support and employee welfare.